Pelatihan Pengembangan Media Matematika Berbasis Budaya sebagai Upaya Peningkatan Profesionalisme Guru-Guru di SD Inpres Adobala dan SD Inpres Pepakkelu - Dominikus Wara Sabon; Patrisius Afrisno Udil; Imelda Hendriani Eku Rimo; Zacharias Angelius Krisnadi Wara Sabon (Jurnal Nasional Pengabdian Masyarakat, 2023)
This activity for the community aims to help elementary school teachers create culture-based learning media as part of learning innovation. Meanwhile, the background for holding this activity is because there is an elementary school mathematics concept related to culture and thus requires culture-based mathematics learning media. Still, elementary school teachers have never developed culture-based mathematics learning media. The methods used in this activity are lecture, discussion, question and answer, demonstration, and practice. The provision of material I is an introduction to Indonesian Realistic Mathematics Learning (PMRI). Presentation of the 2nd material on Adonara ethnomathematics, followed by the 3rd material on elementary school mathematics concepts related to local Adonara culture, to open up the thinking horizons of teachers, making it easier to create appropriate mathematical media. Followed by discussion and questions and answers. The provision of material 4, namely about Model Student Activity Sheets as a learning medium, was followed by a demonstration of the use of culture-based mathematics media that had been prepared by the implementing team in learning several elementary school mathematics concepts and continued with discussion and questions and answers. Material 5 was given, namely about the practice of making culture-based LKPD by teachers and continued with discussion. Furthermore, teachers are also tasked with making LKPD outside of training hours, namely at home, to be presented in the training class the following day.